Electronically tunable phase shifter using CDTAs - Marungreang, Nattaphon; Tanjaroen, Wason; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2009)
The realization of an electronically tunable phase shifter using current differencing transconductance amplifiers (CDTAs) as active components is presented. The proposed filter employs only two CDTAs and one virtually grounded capacitor, which its phase shift can be electronically adjusted by varying the bias current of the CDTA. The circuit also exhibits high-output impedance, which is easy cascading in the current-mode operation. As application example, the current-mode biquad filter based on the proposed CDTA-based phase shifter circuit is also presented. PSPICE simulation results of the proposed circuit and its application are given to confirm the theoretical analysis.